2018
DOI: 10.1007/s10856-018-6044-6
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory response of porous NiTi shape memory alloys fabricated by selective laser melting

Abstract: Porous NiTi scaffolds display unique bone-like properties including low stiffness and superelastic behavior which makes them promising for biomedical applications. The present article focuses on the techniques to enhance superelasticity of porous NiTi structures. Selective Laser Melting (SLM) method was employed to fabricate the dense and porous (32-58%) NiTi parts. The fabricated samples were subsequently heat-treated (solution annealing + aging at 350 °C for 15 min) and their thermo-mechanical properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 45 publications
2
74
0
Order By: Relevance
“…Many studies, which were mainly focused on the compression mode, have been conducted to investigate the mechanical properties of SLM fabricated NiTi parts [ 24 , 29 , 43 , 47 , 49 , 60 , 62 , 67 , 68 , 70 , 85 , 95 , 96 , 97 , 98 , 99 ]. The effect of SLM process conditions on the functional properties of NiTi alloys under compression mode has been well studied and summarized, for example in Ref.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Many studies, which were mainly focused on the compression mode, have been conducted to investigate the mechanical properties of SLM fabricated NiTi parts [ 24 , 29 , 43 , 47 , 49 , 60 , 62 , 67 , 68 , 70 , 85 , 95 , 96 , 97 , 98 , 99 ]. The effect of SLM process conditions on the functional properties of NiTi alloys under compression mode has been well studied and summarized, for example in Ref.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The NiTi alloy is in martensitic phase at low temperatures and in the austenitic phase at high temperatures [4]. A review of the literature showed that different manufacturing processes are used for the machining of NiTi alloy such as laser processing method [5][6][7][8][9][10][11][12][13][14][15][16], electrical discharge machining (EDM) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], electrochemical polishing [32] and abrasive water jet processing method (AWJM) [33,34] for shaping NiTi alloy and also conventional machining methods (Turning [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], milling…”
Section: Introductionmentioning
confidence: 99%
“…In general, as proved by many studies [ 62 , 114 , 115 , 116 ], porous NiTi SMAs exhibit good cell adhesion and biocompatibility, which also depends on the structure of surfaces. For example, Assad et al [ 117 , 118 ] systematically studied the biocompatibility of porous NiTi SMAs by in vitro and in vivo testing, and concluded that the short-term biocompatibility of porous NiTi is comparable to that dense NiTi, moreover it has no potential to produce irritation, systemic toxicity reactions, or sensitization in animal models by in vivo standard allergy potential evaluation.…”
Section: Porous Niti Shape Memory Alloysmentioning
confidence: 99%
“…Thus, powder metallurgy (PM) techniques are generally used from either elements powder or pre-alloyed powder [ 46 , 47 , 48 , 49 , 50 ], including conventional sintering (CS) [ 51 , 52 ], hot isostatic pressing (HIP) [ 53 ] or CF-HIP [ 12 , 54 , 55 ], or sintering at a low gas pressure [ 56 ], SHS [ 57 , 58 ], as well as spark plasma sintering (SPS) [ 59 ] and microwave sintering [ 60 ]. Recently, the additive manufacturing (AM), like selective laser melting (SLM) or electron beam melting (EBM), are preferentially used to fabricate porous NiTi SMAs [ 61 , 62 , 63 , 64 ]. Because the AM technique has advantages of building porous parts with very complex geometries, it is a very cost-effective, energy efficient, and environmentally friendly manufacturing process [ 61 ].…”
Section: Porous Niti Shape Memory Alloysmentioning
confidence: 99%